Referenciação e humor em tiras da personagem Marly - Pinto, Priscila Guimarães (2017)
The research in question aims to investigate the process of (re) construction of referents (discursive-cognitive objects) in the textual genre comic strips, and to observe the function of referential processes for the production of humor in this genre. In this way, it is based on studies of the text in the perspective sociocognitiva, interaction and aims: 1) there investigates the process of referents' reconstruction in the textual type comic strips (RAMOS, 2009, 2011, 2012; NICOLAU, 2010; CAGNIN, 2014; and 2) to observe the function of processes referential systems for the production of the humor in this type. For so much, it looks for backrests – methodological in the studies on referencing (MONDADA & DUBOIS, 2003; MARCUSCHI, 2007; CAVALVANTE, 2012; KOCH & ELIAS, 2013) and on humor (FREUD, 1977; PROOP, 1992; BERGSON 1980) . The corpus that composes this work is constituted by 10 (ten) comic strips of the character Marly, creation of the cartoonist Milson Henriques and collected from the newspaper A Gazeta. The results obtained in the analyses point that: 1) the referents are introduced / evoked, maintained, modified in and it shears imbrication verbal/ imaginary ; 2) the referents, while being recategorized, contribute in basic way to the explosion of the humor in the selected strips.